The challenges of used extensive reading in teaching Malay as a foreign language - Husin, Fazilah (David Publishing Company, 2014)
The ML (Malay Language) is one of the foreign languages taught to students at the DMIT (Department of Malay-Indonesian Translation & Interpretation), HUFS (Hankuk University of Foreign Studies), Yongin Campus. The students here are required to learn both the Malay and Indonesian languages, which are under the same parent language. The students found that it is difficult to identify the differences between the two languages, because most of the linguistic features are highly similar. It is much easier to explain the differences in terms of the terminology and spelling, but trying to explain the writing style or the structure of a sentence is a more challenging task. Thus, ER (extensive reading) activities were undertaken with a view to expose the students to the ML by using various forms of written materials. ER was also a means for students to experience restricted communication in Malay, because the students had very limited opportunities to use the ML outside the classroom. The materials used in this activity were made available for the students in printed form or accessible via the internet. Sub-activities besides reading were conducted in the classroom to complement the lecture. The contact hours were 80 minutes per week and the activity was conducted for seven weeks. Reading is done either individually or as a group depending on the type of material, length and difficulty, or the students’ level of proficiency. Some of the problems or constraints in conducting ER activities include the difficulty in finding materials which are suitable for both learning and maintaining the students’ interest in the reading materials provided.